2022
DOI: 10.3390/microorganisms10071435
|View full text |Cite
|
Sign up to set email alerts
|

Placental Characteristics of a Large Italian Cohort of SARS-CoV-2-Positive Pregnant Women

Abstract: The variety of placental morphological findings with SARS-CoV-2 maternal infections has raised the issue of poor agreement in histopathological evaluation. The aims of this study were: to describe the histopathological placental features of a large sample of SARS-CoV-2-positive women who gave birth in Italy during the COVID-19 pandemic, to analyse the factors underlying these lesions, and to analyse the impact of placental impairment on perinatal outcomes. From 25 February 2020 to 30 June 2021, experienced per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(69 reference statements)
0
9
0
1
Order By: Relevance
“…Di Girolamo et al, in a meta-analysis including 56 studies and 1008 pregnancies, reported that, in pregnant women with SARS CoV-2 infection, a significant proportion of placentas showed histopathologic findings of placental hypoperfusion and inflammation [ 14 ]. On the contrary, according to more recent studies [ 15 , 16 ], COVID-19 did not seem to be associated with specific histopathological findings, and placental abnormalities were not increased in COVID-19 pregnancies compared to controls. However, these studies included a too heterogeneous population, either for timing of infection, the inclusion of maternal preexisting conditions, or pregnancy related complications.…”
Section: Introductionmentioning
confidence: 73%
“…Di Girolamo et al, in a meta-analysis including 56 studies and 1008 pregnancies, reported that, in pregnant women with SARS CoV-2 infection, a significant proportion of placentas showed histopathologic findings of placental hypoperfusion and inflammation [ 14 ]. On the contrary, according to more recent studies [ 15 , 16 ], COVID-19 did not seem to be associated with specific histopathological findings, and placental abnormalities were not increased in COVID-19 pregnancies compared to controls. However, these studies included a too heterogeneous population, either for timing of infection, the inclusion of maternal preexisting conditions, or pregnancy related complications.…”
Section: Introductionmentioning
confidence: 73%
“…These findings include signs of inflammation with villous infiltration and intervillitis, vascular malperfusion and involvement of syncytiotrophoblast cells or other fetal cells [20]. Nonetheless, no specific or pathognomonic placental lesions have been identified for SARS-CoV-2 infection [26,27]. The transplacental transmission to the newborn is rare even when the placenta is positive for SARS-CoV-2, and investigators have postulated different models to explain this protective effect [20,28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chronic histiocytic intervillositis and intervillous fibrin deposition have been related to intrauterine fetal death, early-onset intrauterine growth restriction and newborn neurological symptoms [33]. However, in two wide recent studies, "SARS-CoV-2 placentitis" has been found to have a very low incidence and no significant association with neonatal morbidity and/or intrauterine growth restriction [26,31]. So far, how this lesion may affect the fetus has yet to be elucidated, and the timing of the maternal viral infection may play a key role in determining newborns' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In Italia, fin dall'inizio della pandemia, l'Italian Obstetric Surveillance System (ItOSS https://www.epicentro.iss.it/itoss/) dell'Istituto Superiore di Sanità (ISS) ha avviato uno studio nazionale prospettico populationbased per monitorare le donne in gravidanza con infezione da SARS-CoV-2 ricoverate in ospedale 2 . Oltre 11.000 donne positive sono state arruolate da febbraio 2020 a giugno 2021 e da gennaio a maggio 2022, permettendo di analizzare l'impatto del virus originario, delle varianti Alfa e Omicron sugli esiti di salute materni e perinatali [3][4][5][6][7][8][9] . Lo studio ha confermato che nel periodo dominato dalla variante Omicron la vaccinazione protegge dalle forme gravi di Covid-19 e da esiti materni e perinatali sfavorevoli 9 .…”
Section: Lettere Lettereunclassified